Revisiting the Concept of 'Qaulan Sadidan' (Truthful Speech) in the Qur'an: A Framework for Ethical Communication in the Post-Truth Era - Gantira, Erlan (Sekolah Tinggi Agama Islam Kuningan, 2025)
The contemporary post-truth era has fundamentally challenged traditional notions of truth, honesty, and ethical communication, with misinformation proliferating across digital platforms at an unprecedented rate. In this context, the Qur'anic concept of 'qaulan sadidan' (truthful speech) offers a timeless ethical framework that transcends cultural and temporal boundaries. This study revisits the concept of qaulan sadidan as articulated in Surah al-Nisa' (4:9) and Surah al-Ahzab (33:70) to develop a comprehensive framework for ethical communication applicable to contemporary challenges. Employing a qualitative methodology with thematic tafsir analysis and content analysis of classical and modern Islamic scholarly works, this research examines how qaulan sadidan encompasses not merely factual accuracy but also constructive intent, contextual appropriateness, and beneficial outcomes. The study reveals that qaulan sadidan operates on three fundamental dimensions: epistemological (truth-telling), ethical (moral responsibility), and pragmatic (effective communication). Furthermore, this research demonstrates how the principles derived from qaulan sadidan can address critical challenges in the post-truth era, including digital misinformation, polarized discourse, and the erosion of public trust. The findings indicate that implementing qaulan sadidan principles requires both individual commitment to truthfulness and systemic reforms in media literacy, digital platform governance, and educational curricula. This study contributes to Islamic communication ethics scholarship while offering practical solutions for navigating the complex information ecosystem of the twenty-first century.